(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
His study aims to analyze the dimensions of Service Quality on Student Satisfaction at STTA Yogyakarta. The population in this study were students of the Electrical Engineering Study Program with a total of 66 respondents as samples in the study. This research method uses quantitative methods in the form of a questionnaire. The tool used to analyze the research data is multiple linear regression. Validity test which shows that the statement in this study is valid, while the reliability test using Cronbach Alpha is declared reliable. Based on the research, the results of the t test show that the physical evidence variable has a significant effect on customer satisfaction with a sig value of 0.047 less than 0.05, the reliability variable has a significant effect on customer satisfaction with a sig value of 0.041 less than 0.05, the responsiveness variable has a significant effect on customer satisfaction with a value of sig 0.031 less than 0.05, the assurance variable has a significant effect on customer satisfaction with a sig value of 0.024 less than 0.05, the empathy variable has a significant effect on customer satisfaction with a sig value of 0.044 less than 0.05. So partially the variables of physical evidence, reliability, responsiveness, assurance and empathy have a significant effect on satisfaction.